Gallium Antimonide Thermophotovoltaic: Simulation and Electrical Characterization under Different Spectral Filtration Wavelengths - Suliza W.E.; Rashid W.A.; Jamaludin M.Z.; Rahman N.A.; Gamel M.M.A.; Lee H.J.; Ker P.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cells; Computer software; Cytology; Efficiency; Gallium; III-V semiconductors; Photonics; Semiconducting antimony compounds; Verification; Waste heat; Electrical characteristic; Electrical characterization; Experimental characterization; Illumination conditions; Physical parameters; Standard test condition (STC); Thermophoto voltaic cells; Waste heat harvesting; Gallium compounds